PENGGUNAAN METODE SYNTHETIC STRUCTURAL ANALYTICAL (SAS) UNTUK MENINGKATKAN KAPASITAS MEMBACA AWAL PADA SISWA KELAS 1 SD - Feby Tiana Permana; Asep Samsudin (STKIP Subang, 2022)
Through the use of Synthetic Analytical Structural (SAS) methods, this research seeks to enhance the implementation of the first reading learn and improve processes. the outcomes of using Synthetic Analytic Structure (SAS) Methods to enhance beginners' reading abilities SDN Cikalong Class I Students 2. Synthetic analytic structure (SAS) methods are used to improve the reading process and initial learning outcomes. This is done through classroom activities and qualitative research. Collaboration between teachers and students for classroom action research. The findings demonstrated that the use of Synthetic Analytical Structural Methods (SAS) to create wholesome, spotless, and lovely Ambient materials could enhance students' beginning reading abilities. It can be inferred from pre-cycle observations that the level of learning outcomes for reading in a tidy, healthy, and attractive environment is still below average or low, i.e. e. 65.7% of students who have not yet graduated from school at the designated KKM. The average score must be at least 70. In cycle II, the grade point average is 66 points higher than it was in cycle I, which was only 65 points, and the student pass rate is 65 points higher than it was in cycle I, which was not 65 points. This information can be gleaned from each student's grade results, which are completed in accordance with the established KKM, which is 70.